Terapi Murottal Al Mulk terhadap Penurunan Tingkat Kecemasan pada Ibu Bersalin - Nabila, Alifia Putri; Sulastri, Sulastri (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of Al Mulk murottal therapy in reducing anxiety levels in mothers giving birth. The method used in this research is quasi-experimental with a two-group pretest-posttest design. The research results showed that applying Al-Mulk murottal therapy obtained a p-value of 0.000. The conclusion is that the Al-Mulk murottal therapy intervention is effective because it can reduce the level of anxiety in mothers giving birth. Keywords: Mother giving birth, Anxiety, Murottal Al Mulk Therapy